World panorama of remotely operated underwater robots (ROV) research (Research, Society and Development, 2021)
Remotely operated underwater vehicles (ROVs) are part of a group of technologies that have been increasingly used as a tool in scientific research. The applications for these vehicles are vast and the work aims to present analyzes of socioeconomic and environmental scope, bringing a world panorama on scientific research that includes ROVs. A data matrix with literary research was created, including 78 published documents. The main information evaluated were continents and countries that publish works, partnerships between countries, whether there was funding for the project, the area of study and application and the characteristics of the ROV used, especially if it was developed exclusively for the project or if existing equipment was purchased. We note that the most developed countries are the ones that invest the most in technology, both in number of publications and in funding, a fact that can be justified by the commitment of government entities to make constant contributions to scientific research. On the other hand, countries like Brazil and China have been showing excellent results and growth in the application of resources in science and technology. The benefits of investing in this technology are reflected throughout society, generating jobs, contributing to the national economy, and encouraging research, knowledge, and science.